2023
DOI: 10.5194/hess-27-3143-2023
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal soil moisture and crop yield prediction with fifth-generation seasonal forecasting system (SEAS5) long-range meteorological forecasts in a land surface modelling approach

Theresa Boas,
Heye Reemt Bogena,
Dongryeol Ryu
et al.

Abstract: Abstract. Long-range weather forecasts provide predictions of atmospheric, ocean and land surface conditions that can potentially be used in land surface and hydrological models to predict the water and energy status of the land surface or in crop growth models to predict yield for water resources or agricultural planning. However, the coarse spatial and temporal resolutions of available forecast products have hindered their widespread use in such modelling applications, which usually require high-resolution i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 69 publications
(110 reference statements)
2
8
0
Order By: Relevance
“…Several past studies also indicated the underestimation of ET and GPP in CLM5 compared to observations (Boas et al, 2023;Strebel et al, 2023;Cheng et al, 2021;Birch et al, 2021), which we confirm in this study. Parameter improvements could also alleviate these general underestimations of GPP and ET across PFTs, especially during summer (Dagon et al, 2020).…”
Section: Pft-specific Evaluationsupporting
confidence: 90%
See 3 more Smart Citations
“…Several past studies also indicated the underestimation of ET and GPP in CLM5 compared to observations (Boas et al, 2023;Strebel et al, 2023;Cheng et al, 2021;Birch et al, 2021), which we confirm in this study. Parameter improvements could also alleviate these general underestimations of GPP and ET across PFTs, especially during summer (Dagon et al, 2020).…”
Section: Pft-specific Evaluationsupporting
confidence: 90%
“…Recent studies already found discrepancies between LSM simulations of ET and GPP and observations collected in the field and from remote sensing. For instance, these discrepancies are evident in their magnitude and variability (De Pue et al, 2023;Boas et al, 2023;Cheng et al, 2021;Strebel et al, 2023) and their response to drought (Ukkola et al, 2016;Wu et al, 2020;Green et al, 2024). Therefore, assessing the accuracy of LSMs in representing observed GPP and ET fluxes is crucial to test and improve our current understanding of ecosystem process variability and identify the limitations of state-of-the-art LSMs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These products typically use partial differential formulations to describe atmospheric states and then apply numerical approximations to solve for the states at a specific resolution. Meanwhile, these products have provided valuable seasonal precipitation forecasts to support various applications, including those related to agriculture [7], hydrology [8], and the environment [9].…”
Section: Introductionmentioning
confidence: 99%